DNA Barcoding untuk Autentikasi Produk Hiu Segar dari Perairan Nusa Tenggara Barat: DNA Barcoding for Fresh Shark Products Authentication from West Nusa Tenggara Waters - Alsere Bardian Sahaba, Muhammad; Abdullah, Asadatun; Nugraha, Roni (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Shark and ray fisheries in Indonesia, including Tanjung Luar, West Nusa Tenggara, face considerable challenges where shark and ray populations continue to decrease. Sharks are particularly vulnerable to overfishing and extinction due to slow sexual maturity and low fecundity. Shark meat and fin are generally in demand by consumers; however, other shark products are not separately recorded in trade statistics, making them difficult to identify based on morphological indicators. As an alternative, the DNA barcode method can be applied. This study aims to identify rare shark species recorded on CITES that have landed at the port of NTB using the DNA barcoding method. The research includes the stages of DNA isolation, DNA amplification, sequencing and bioinformatics analysis. The results of sequencing and bioinformatics analysis showed Sphyrna lewini and Carcharhinus falciformis DNA species in samples with 99-100% similarity. These results show that the use of sharks that are included in the CITES list is still often carried out, so it is necessary to implement stricter regulations and transfer public knowledge so that endangered shark species can be preserved.